Clinical pathways and outcomes of patients with Barrett's esophagus in tertiary care settings: a prospective longitudinal cohort study in Australia, 2008–2016. Issue 8 (12th December 2020) - Na, Renhua; Miura, Kyoko; O'Brien, Suzanne; Eslick, Guy D; Kendall, Bradley J; Hourigan, Luke F; Bourke, Michael; Cox, Michael R; Farrokhzadi, Laal; Levert-Mignon, Angelique J; Barbour, Andrew P; Clemons, Nicholas J; et al.
Summary: Background: Clinical services for Barrett's esophagus have been rising worldwide including Australia, but little is known of the long-term outcomes of such patients. Retrospective studies using data at baseline are prone to both selection and misclassification bias. We investigated the clinical characteristics and outcomes of Barrett's esophagus patients in a prospective cohort. Methods: We recruited patients diagnosed with Barrett's esophagus in tertiary settings across Australia between 2008 and 2016. We compared baseline and follow-up epidemiological and clinical data between Barrett's patients with and without dysplasia. We calculated age-adjusted incidence rates and estimated minimally and fully adjusted hazard ratios (HR) to identify those clinical factors related to disease progression. Results: The cohort comprised 268 patients with Barrett's esophagus (median follow-up 5 years). At recruitment, 224 (84%) had no dysplasia, 44 (16%) had low-grade or indefinite dysplasia (LGD/IND). The age-adjusted incidence of esophageal adenocarcinoma (EAC) was 0.5% per year in LGD/IND compared with 0.1% per year in those with no dysplasia. Risk of progression to high-grade dysplasia/EAC was associated with prior LGD/IND (fully adjusted HR 6.55, 95% confidence interval [CI] 1.96–21.8) but not long-segment disease (HR 1.03, 95%CI 0.29–3.58). Conclusions: These prospective data suggest presence of dysplasia is a stronger predictor of progression to cancer than segment length in patients with Barrett's esophagus.